2023
DOI: 10.3389/fpsyg.2023.1129961
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of female bisexual student-athletes in China: An interpretative phenomenological analysis

Abstract: IntroductionMany scholars have explored the participation of LGBTQ individuals in sports. However, these studies have either categorized homosexuality and bisexuality together or focused only on lesbian, gay, or transgender individuals. There is a lack of research in the literature on bisexual individuals’ sports participation and an even more significant lack of Asia perspectives. Therefore, this qualitative study is aimed to explore the experiences of female bisexual student-athletes in China.MethodsSemi-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…In China, very few LGBTQ athletes have come out publicly. Despite this, recent research has shown that female bisexual student-athletes are better able to explore intimate relationships after prolonged exposure to athletic training and competition (Xiang et al, 2023) and that coaches in China become more accepting and tolerant of student-athletes of different sexual orientations (Tseng and Sum, 2021). These findings suggest that sport can be a more welcoming environment for sexual minorities.…”
Section: Contextualization Of Gendered Sport and Sexuality In Chinamentioning
confidence: 99%
“…In China, very few LGBTQ athletes have come out publicly. Despite this, recent research has shown that female bisexual student-athletes are better able to explore intimate relationships after prolonged exposure to athletic training and competition (Xiang et al, 2023) and that coaches in China become more accepting and tolerant of student-athletes of different sexual orientations (Tseng and Sum, 2021). These findings suggest that sport can be a more welcoming environment for sexual minorities.…”
Section: Contextualization Of Gendered Sport and Sexuality In Chinamentioning
confidence: 99%